Pengaruh Kualitas Layanan Terhadap Kepuasan Pelanggan Perusahaan Rh Interior - Miko; Dewi Anggraini; A. Mahendra; Fauzi A.M. Hutabarat (Yayasan Literasi Sains Indonesia, 2022)
Service quality is a criterion for a company in terms of providing services that have a direct impact on satisfaction according to their needs and desires. While customer satisfaction is a feeling of pleasure or disappointment of someone who appears after seeing the performance of an item or service offered by a party. The purpose of service quality itself is to foster consumer confidence in the products or services offered so that customers feel that all their needs are cared for, and to avoid demands/complaints from customers. The formulation of the problem in this study,